Pemanfaatan Cendawan Mikoriza Arbuskular Untuk Mereduksi Kadar Pb dan Cd pada Lahan Sawah Serta Pengaruhnya Terhadap Pertumbuhan Tanaman Selada - Marhamah Nadir; Syamsia Syamsia; Sartika Laban (Universitas Hasanuddin, 2018)
Pb and Cd are two types of heavy metal that has been widely contaminates agricultural land. Pollution on agricultural land led to a decrease in productivity, disruption of the ecological balance and impaired human health. The research aims to identify and detect the content of heavy metals Cd and Pb in the soil and measure the effectiveness of the arbuscular mycorrhizal veskular withstand heavy metals in lettuce plants. Soil samples were collected in the Village Sudiang Makassar City using stratified sampling and purposive sampling methods. Sampling points are distinguished based on the distance from the highway, which is 15 meters and 30 meters. Analysis of heavy metal content in soil carried Soil Laboratory BPTP Maros. The study based on a randomized block design in a factorial 2 factors. The first factor was soil sampling and the second factor was the provision of mycorrhizae. Based on the survey results revealed that the content of Pb and Cd in soil belt of northern South Sulawesi has passed the threshold. Due to the reduced content of Pb and Cd after treatment arbuscular mycorrhizal fungi but the decline is not significant compared with no treatment mycorrhizae. The content of Cd and Pb in plants of lettuce grown in the various media and the addition of CAM treatments above the threshold concentration safe for consumption.